Experimental study on flow-induced motion and energy conversion for two triangular prisms in tandem arrangement - Shao, Nan; Xu, Guobin; Wu, Zhichuan; Liu, Fang; Yan, Xiang; Wang, Xiaoqun (Frontiers in Energy Research, 2023)
Experimental tests on two tandem triangular prisms were accomplished in synergistic flow-induced motion (FIM) to collect ocean current energy (OCE) with varied spacing ratios and Reynolds number ranges. Typical FIM responses and energy conversion are discussed and presented. The effects of parameters (system stiffness, spacing ratio, and load resistance) were considered to improve the energy harvesting of the system. The main findings can be summarized as follows: 1) with varied spacing ratios between the two tandem prisms, the active power (Pharn) was up to 1.95 times that of the single triangular prism (STP); 2) In general, the harnessed OCE capacity of the upstream triangular prism (UTP) was improved, while the energy harvesting of the downstream triangular prism (DTP) was suppressed by the interaction of the two prisms, 3) In the tests, electricity was generated at U = 0.516 m/s, and the active power, which consistently increased as flow velocity increased, reached Pharn = 32.24 W, with a corresponding efficiency of ηharn = 10.31%; and 4) The best energy conservation performance for harvesting the OCE occurred at L/D = 5, and the optimal load resistance was found at RL = 11 Ω.